Analysis and Evaluation of Conceptual Model for Health-Related Quality of Life Employing Fawcett and DeSanto-Madeya's Critique Framework. (October 2019) - Jang, Min Kyeong; Vincent, Catherine
Abstract : Health-related quality of life is increasingly used as a predictor in nursing research and practice because its multidimensional constructs encompass the holistic spectrum of care. This article comprehensively analyzes and evaluates the conceptual model of health-related quality of life of Ferrans and colleagues using Fawcett and Desanto-Madeya's 2013 framework. The model encompasses all relevant concepts and propositions in its theoretical foundation while maintaining consistency with the nursing metaparadigm. Also, the model has comprehensive content, appropriate context, and social and theoretical significance. To maximize the model's empirical and pragmatic adequacy, researchers should carefully define the variables associated with each concept.